Flow experience in Qur’an memorization among university student living in pesantren - Falasifah, Malisa (Psikoislamika: Jurnal Psikologi Islam, 2025)
Flow is a state of optimal experience characterized by full concentration, intrinsic motivation, and a sense of control during an activity. This study explores the flow experience of female university students in Islamic boarding schools (pesantren) while memorizing the Qur’an. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with five respondents and analyzed manually using Interpretative Phenomenological Analysis (IPA). The findings revealed three superordinate themes: absorption in memorization, effortless control supported by spiritual discipline, and intrinsic reward linked to faith and fulfillment. These themes reflect how respondents experience deep focus and enjoyment while engaging in Qur’an memorization. Several internal factors such as personal motivation, clarity of goals, and emotion regulation enhanced their ability to enter the flow state. At the same time, external factors like quiet environment, peer encouragement, sand parents support also played a significant role. Respondents adopted specific strategies to sustain flow, including seeking meaning in memorized verses, environmental preparation and emotional regulation. The study highlights the unique spiritual and cultural context of Qur’an memorization, showing that flow can be deeply influenced by religious commitment and community support. These results contribute to the understanding of flow in non-Western, faith- based learning environments and provide insight into how spiritual practices can support optimal psychological experiences in education. Keywords: Flow Experience; Qur’an Memorization; Santri; University Students; Pesantren. Copyright ©2025. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0